Amorphous Cobalt Boride Nanosheets Directly Grown on Nickel Foam: Controllable Alternately Dipping Deposition for Efficient Oxygen Evolution. Issue 14 (18th July 2019) - Jiang, Yuanyuan; Fang, Yating; Chen, Chuanxia; Ni, Pengjuan; Kong, Biao; Song, Zhongqian; Lu, Yizhong; Niu, Li
Abstract: This study provides a unique method for the rapid deposition of amorphous Co−B nanosheets on Ni foam (Co−B/NF) by alternatively dipping Ni foam into cobalt salt and borohydride solutions. The as‐prepared Co−B/NF can act as a highly efficient electrocatalyst for the oxygen evolution reaction (OER). The catalyst affords a current density of 20 mA cm −2 at 265 mV overpotential during the OER in 1.0 M KOH solution, ranking it among the best reported nonprecious OER electrocatalysts. This strategy for constructing electrocatalysis electrodes prevails over the conventional method of drop‐coating metal boride dispersions on the electrode, having better intrinsic stability and fully exposed active site surfaces. Given the low cost, ease of fabrication, good controllability, and high OER electrocatalytic activity and stability, Co−B/NF has great potential as a high‐performance anode catalyst for water splitting. Abstract : Lucky dip : The hierarchical structure of Co−B amorphous nanosheets grown on nickel foam (NF) results in a notably high electrocatalytic activity for water oxidation.